(untitled) (Global Journal of Science Frontier Research, 2025)
This paper investigates the propagation speed of darkness redefined not as an absence of light but as a physical boundary whose dynamics extend the limits of illumination causality Using wave front level-set theory geometric projection analysis and a r einterpretation of spacetime geometry we der ive a generalized expression for the darkness-front velocity and demonstrate that it can exceed the vacuum speed of light 299 792 458 m s We present a unified formulation discuss the non-material nature of this boundary and propose experimental methods to test these effects The conclusion is reached that darkness as a non-material but ontologically significant boundary can propagat e faster than any finite physical velocity without violating relativistic causality